EFFECT OF POTASSIUM HYDROXIDE CONCENTRATION AS A CATALYST ON THE YIELD OF COCONUT OIL (Cocos nucifera) TRANSESTERIFICATION - Chaleb Paul Maanari; Sanusi Gugule; Feti Fatimah; Aisyiah Restutiningsih Putri Utami; Mustapa Mustapa; Stefan Marco Rumengan; Miftahul Jannah; Jakub Saddam Akbar; Djois Sugiaty Rintjap (Tanjungpura University, 2023)
Research has been carried out on the effect of potassium hydroxide catalyst concentration on the yield of coconut oil (Cocos nucifera) transesterification and continued to characterize the reaction results. The concentration of potassium hydroxide used was 1, 2, and 3% by weight of coconut oil with ethanol as the reactant. The data processing used was the one-way analysis of variation and its characterization from a physicochemical perspective, followed by the analysis of gas chromatography-mass spectroscopy (GCSM) and infrared spectrophotometry. Based on the data processing results, potassium hydroxide concentrations of 1, 2, and 3% did not affect the yield of the transesterification reaction of coconut oil, and the results were 74.5264%, 71.9330%, and 69.0420%. The characterization results show that the physicochemical properties of the reaction products, such as acid number, density, and viscosity, comply with the Indonesian National Standard (SNI) for biodiesel. The results of the GCMS analysis showed that nine peaks were dominated by ethyl laurate.